Playing with or next to? The nuanced and complex play of children with impairments. Issue 10 (3rd October 2019) - Burke, Jenene; Claughton, Amy
ABSTRACT: This paper examines play as a fundamental children's activity, giving particular attention to the inclusion of children with impairments at play and children's shared constructions of their playworlds. Children with impairments are customarily portrayed as incompetent, unskilled or deficient in their play, thus being positioned on the margins (or, as 'who's out'?) of mainstream discourses. On the other hand, non-impaired children are usually regarded as competent players, who play in 'normal' ways (as 'who's in'?). Little attention is afforded to noticing skilful or proficient play by children with impairments and including their perspectives in play research. The Social Model of Childhood Disability offers a perspective for considering 'disabled childhoods' and framing enquiry into the culturally-constructed playworlds of children with impairments. Evidence from two ethnographic studies that examine children with impairments at play is discussed, employing vignettes that utilise data from researcher and teacher observation notes. The authors document specific play interactions related to individual experiences and interests and explore how children work together and alone to create meaningful play interactions. The notion that play for children is a mutual, shared and inclusive cultural experience is supported in this paper.